Conselhos escolares e resultados de avaliação em larga escala (IDEB): uma interlocução possível sobre qualidade da educação escolar? - Lima, Waldísia Rodrigues de (2011)
The objects of study of this work have been the municipal school councils (CEs) of the municipality of Cubatão. The problem under investigation can be summarized in the following question: What is the role that large evaluation, represented by the IDEB, plays in the CEs discussions. The aim of the study is to investigate the CEs actions regarding to the formal elementary education quality, in this case, represented by a external evaluation. The research introduces two strong justifications for that. First: the need for further analysis on the effects, the consequences of external evaluation on the school taking into account the publicity given to the its results, the repercussion for the municipal management and placing of the school under monitoring in consequence of the results. Second: the need of examining how the CE works, what can be an indicator of its consolidation as an instrument for the democratic management. The field work is concentrated in there municipal schools CEs. The study presents a qualitative approach, analyzing the guiding principle of the CEs, the IDEB and the content of CEs meeting minutes. In addition, we analyzed questionnaires applied on CEs and to 47 school principals in the same municipality. Several authors that discuss the attainments of collegiate and the public management support this work: Barroso (1996), Bordignon (2004), Dourado (2004), Gadotti (2004), Martins (2005), Scheinvar & Algebaile (2005), Silva (2006), Freire (2007), Libâneo (2008), Lima (2008) and Saviani (2009). Also, we will take into account other authors that analyze the educational policy evaluation, like:Vianna (2000), Afonso (2009) e Freitas (2009). The data analyzed show that the CEs under investigation behave as democratic management instrument. They do not explicity discuss fundamental issues to guarantee the schooling education quality: the use of financial resources from federal and municipal programs with pegagogic aims and focused on the student; disciplinary issues like the collective elaboration of conduct codes; demand for technical administrative personnel and teachers to address the lack of personnel, monitoring and decision on educational projects, therefore, they show envelopment in issues relevant to the schooling scope.